Assessing the validity of discourse analysis: transdisciplinary convergence - Jaipal-Jamani, Kamini (Cultural studies of science education, 2014)
Research studies using discourse analysis approaches make claims about phenomena or issues based on interpretation of written or spoken text, which includes images and gestures. How are findings/interpretations from discourse analysis validated? This paper proposes transdisciplinary convergence as a way to validate discourse analysis approaches to research. The argument is made that discourse analysis explicitly grounded in semiotics, systemic functional linguistics, and critical theory, offers a credible research methodology. The underlying assumptions, constructs, and techniques of analysis of these three theoretical disciplines can be drawn on to show convergence of data at multiple levels, validating interpretations from text analysis.